(untitled) (Journal of Naval Architecture and Marine Engineering, 2021)
Monitoring of structural vibrations and operational modal analysis are clearly essential to effectively control structural safety and the operational behavior of tidal current turbines. In order to satisfy industrial requirements, generally related to a mass gain problem, hybridization provides an excellent method to improve the breaking strength of composite materials, while keeping adequate mechanical performance for marine renewable energy applications. In this context, this work aims to study the structural modal analysis of a tidal turbine nozzle and the effect of hybrid materials (carbon/Glass) on the natural frequencies and corresponding mode shapes of the three laminates. The modal analysis was calculated by the Finite Element Method using ABAQUS software. According to the results, the stacking sequence has a considerable impact on the natural frequency of the nozzle. Furthermore, it is also found that the resonance effect does not appear for the three laminates under investigation.